2017
DOI: 10.1002/jmv.24904
|View full text |Cite
|
Sign up to set email alerts
|

Association of clinical and serological parameters of systemic lupus erythematosus patients with Epstein‐Barr virus antibody profile

Abstract: Epstein-Barr viral infection is one of the known environmental factors involved in development of Systemic Lupus Erythematous (SLE). Though not much is known about the exact role of Epstein-Barr virus (EBV) in SLE pathogenesis, the theory of switching of lytic and lysogenic cycles of EBV in memory B cells fits well with the periods of waning disease activity and intermittent flares in SLE patients. In this study, we investigate the association of EBV antibody profile with clinical and serological parameters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
(17 reference statements)
3
23
0
Order By: Relevance
“…Significant differences were observed not only in the prevalence of VCA-IgA ( P < 0.001), but also in the prevalence of VCA-IgG and EBNA1-IgG antibodies ( P < 0.01) between the 6 – 10 years old SLE patients and controls. The overall EBV past infection with common chronic active infection (as high prevalence of VCA IgA) in pediatric SLE patients in our study provides, on another hand, evidence for the reports [ 6 , 28 ] that EBV infection may pay a big role or being a trigger in the pathogenesis of SLE. For other autoimmune diseases, it seemed that the association with EBV was not as strong as that with SLE patients ( P = 0.039).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Significant differences were observed not only in the prevalence of VCA-IgA ( P < 0.001), but also in the prevalence of VCA-IgG and EBNA1-IgG antibodies ( P < 0.01) between the 6 – 10 years old SLE patients and controls. The overall EBV past infection with common chronic active infection (as high prevalence of VCA IgA) in pediatric SLE patients in our study provides, on another hand, evidence for the reports [ 6 , 28 ] that EBV infection may pay a big role or being a trigger in the pathogenesis of SLE. For other autoimmune diseases, it seemed that the association with EBV was not as strong as that with SLE patients ( P = 0.039).…”
Section: Discussionsupporting
confidence: 71%
“…In the meta-analysis of 25 case control studies of EBV and SLE, Hanlon P et al [ 26 ] reported that the seroprevalence of EBV VCA-IgG, IgA, and EA/D IgG antibodies, though possibly not anti-EBNA-1, were significantly higher in cases than controls. However, the study by Chougule D et al [ 6 ] showed that the antibodies levels of EBV VCA-IgG, VCA-IgM, and EBNA-1 IgG in SLE patients were significantly higher than that in healthy controls. Furthermore, a correlation was also shown between EBV infection and disease activity of SLE [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(36) This promotes the production of type I IFNs, pro-inflammatory cytokines and autoantibodies via the TLR3 signaling pathway. (19,34,36) There is a large number of studies that have addressed the relationship between EBV and the development of autoimmune diseases such as systemic lupus erythematosus (37,38) and its exacerbations (39); rheumatoid arthritis (40); type I diabetes mellitus (41); Sjogren's syndrome (42); autoimmune thyroiditis (43); autoimmune hepatitis (44); systemic sclerosis (18); transplant rejection due to viral reactivation (45); autoimmune heart disease (46)(47)(48); adverse drug reactions (49,50); Parkinson's disease (51); and MS. (3,10) Multiple sclerosis MS is an autoimmune disease of the central nervous system with a course that is difficult to predict in each patient. It is characterized by multiple foci of inflammation, demyelination, axonal injury, fibrosis, grey matter involvement and neurodegeneration.…”
Section: Ebv and Autoimmune Diseasesmentioning
confidence: 99%
“…in the pathogenesis of a variety of autoimmune disorders with the hallmark of inducing the production of autoantibodies in the host 10 . Cytomegalovirus (CMV) infections were correlated with the induction and expansion of a proinflammatory CD4 + /CD28 − T cells in RA patients 11 ; and Epstein-Barr virus (EBV) was regarded as an important trigger in the pathogenesis of SLE as evidenced by the co-existence of anti-viral capsid antigen IgG and anti-dsDNA antibodies in the patients 12 . The relationship between leptospirosis and the development of SARDs is unclear; we thus conducted a longitudinal nationwide retrospective cohort study to investigate the occurrence of leptospirosis and the risk of developing SARDs subsequently in the same patients.…”
mentioning
confidence: 99%